Charge collection efficiency, underlying recombination mechanisms, and the role of electrode distance of vented ionization chambers under ultra-high dose-per-pulse conditions. (December 2022) - Kranzer, Rafael; Schüller, Andreas; Gómez Rodríguez, Faustino; Weidner, Jan; Paz-Martín, Jose; Looe, Hui Khee; Poppe, Björn
Highlights: Deeper understanding of the charge collection efficiency of ionization chambers. Simulation of the charge collection efficiency including charge multiplication. Application of ionization chambers under ultra-high dose rate electron beams. Promising tool for real-time dosimetry in FLASH radiotherapy. Abstract: Purpose: Investigating and understanding of the underlying mechanisms affecting the charge collection efficiency (CCE) of vented ionization chambers under ultra-high dose rate pulsed electron radiation. This is an important step towards real-time dosimetry with ionization chambers in FLASH radiotherapy. Methods: Parallel-plate ionization chambers (PPIC) with three different electrode distances were build and investigated with electron beams with ultra-high dose-per-pulse (DPP) up to 5.4 Gy. The measurements were compared with simulations. The experimental determination of the CCE was done by comparison against the reference dose based on alanine dosimetry. The numerical solution of a system of partial differential equations taking into account charge creations by the radiation, their transport and reaction in an applied electric field was used for the simulations of the CCE and the underlying effects. Results: A good agreement between the experimental results and the simulated CCE could be achieved. The recombination losses found under ultra-high DPP could be attributed to a temporal and spatial charge carrier imbalance and the associated electric field distortion. With ultra-thin electrode distances down to 0.25 mm and a suitable chamber voltage, a CCE greater than 99 % could be achieved under the ultra-high DPP conditions investigated. Conclusions: Well-guarded ultra-thin PPIC are suited for real-time dosimetry under ultra-high DPP conditions. This allows dosimetry also for FLASH RT according to common codes of practice, traceable to primary standards. The numerical approach used allows the determination of appropriate correction factors beyond the DPP ranges where established theories are applicable to account for remaining recombination losses.